(untitled) (Conferencea, 2024)
For the practical solution of the problem of building tolerance in the world, the field of education is considered to be of strategic importance. In particular, arousing interest in the problem of tolerance is defined as the most urgent task of the educational system - at the level of one’s own society and at the international level. In itself, such a global problem requires the efforts of pedagogic educational institutions in cooperation with educational management bodies, parents, and public representatives to educate tolerance in human relations.